One-Pot Bottom-Up Synthesis of SiO2 Quantum Dots and Reduced Graphene Oxide (rGO) Nanocomposite as Anode Materials in Lithium-Ion Batteries - Sanjaya Brahma; Cheung-Yi Wang; Yi-Hsuan Huang; Wen-Feng Lin; Jow-Lay Huang (C)
Here, crystalline SiO2 quantum dots (QDs) of 3–5 nm size were grown within the layers of reduced graphene oxide (rGO) by a solution mode chemical growth process at a relatively low temperature (100 °C). The composite was applied as a negative electrode in a Li-ion half-cell battery and the electrochemical investigation confirmed a distinct first-cycle discharge/charge capacity (~865 mAhg−1/387 @ 51 mAg−1). The battery could retain a capacity of 296 mAhg−1 after 60 charge/discharge cycles with 99% coulombic efficiency. Furthermore, at a high current rate of 1.02 Ag−1, the battery was able to display an apparent rate capability (214.47 mAhg−1), indicating the high chemical and mechanical stability of the composite at a high current rate. A structural analysis revealed clear distinct diffraction peaks of SiO2 and high-resolution transmission electron microscopy images showed discrete atomic planes, thereby confirming the growth of crystalline SiO2 QDs within the layers of rGO.